2016
DOI: 10.1371/journal.pntd.0004385
|View full text |Cite
|
Sign up to set email alerts
|

Differential Diagnosis of Skin Ulcers in a Mycobacterium ulcerans Endemic Area: Data from a Prospective Study in Cameroon

Abstract: BackgroundClinical diagnosis of Buruli ulcer (BU) due to Mycobacterium ulcerans can be challenging. We aimed to specify the differential diagnosis of skin lesions in a BU endemic area.MethodWe conducted a prospective diagnostic study in Akonolinga, Cameroon. Patients presenting with a skin ulcer suspect of BU were included. M. ulcerans was detected using swabs for Ziehl-Neelsen staining, PCR and culture. Skin punch biopsies were taken and reviewed by two histopathologists. Photographs of the lesions were taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 18 publications
(20 reference statements)
0
26
0
Order By: Relevance
“…Between October 2011 and December 2013, 367 patients were included in the study, out of 447 screened, and 364 were finally analyzed (3 secondary exclusions due to missing clinical data), corresponding to 422 lesions, of which 381 were ulcerative (90.3%). Detailed patient flow is presented elsewhere [ 11 ]. There were more inclusions during the first half of the study period compared to the second half (215 vs. 110).…”
Section: Resultsmentioning
confidence: 99%
“…Between October 2011 and December 2013, 367 patients were included in the study, out of 447 screened, and 364 were finally analyzed (3 secondary exclusions due to missing clinical data), corresponding to 422 lesions, of which 381 were ulcerative (90.3%). Detailed patient flow is presented elsewhere [ 11 ]. There were more inclusions during the first half of the study period compared to the second half (215 vs. 110).…”
Section: Resultsmentioning
confidence: 99%
“…It is thus likely that these PCR negative patients did not have BU. Lesions on the lower limbs have a broader range of etiologies with proportionally less BU [ 4 , 24 ]. The clinical suspicion for BU can moreover be broadened since 10.0% of patients clinically diagnosed as non-BU in our study turned out to have BU by PCR, as we reported before [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several diseases caused by skin some of that are as follows Scabies is a skin condition caused by tiny mites called Sarcoptes scabiei 4 , Pyoderma is a skin infection caused by bacteria 5 , Fungal infection includes infections such as ringworm or dermatophytosis caused by lipophilic yeasts & Malassezia Species, Tropical ulcer is a chronic ulcerative skin lesion thought to be caused by polymicrobial infection 6 and Hyperpigmentation associated with inflammatory skin lesions such as acne 7 .…”
Section: Skin Diseasementioning
confidence: 99%